Micro-leakage at the implant-abutment interface with different tightening torques in vitro (Journal of Applied Oral Science, 2012)
OBJECTIVES: This study evaluated the microleakage at the implant/abutment interface of external hexagon (eH) implants and abutments with different amounts of bacteria and tightening torques. MATERIAL AND METHODS: A bacterial suspension was prepared to inoculate the implants. The first phase of this study used nine EH implants and abutments that were divided into three groups with different amounts of bacterial suspension (n=3): V0.5: 0.5 µL; V1.0: 1.0 µL e V1.5: 1.5 µL, and tightened to the manufacturer's recommended torque. The second phase of this experiment used 27 assemblies that were similar to those used in the first phase. These samples were inoculated with 0.5 µL of bacterial suspension and divided into three groups (n=9). T10: 10 Ncm; T20: 20 Ncm and T32: 32 Ncm. The samples were evaluated according to the turbidity of the broth every 24 hours for 14 days, and the bacteria viability was tested after that period. The statistical evaluation was conducted by Kruskal-Wallis testing (p